System productivity and economics influenced by residue and potassium management in maize (Zea mays)-wheat (Triticum aestivum) rotation - M, RAGHAVENDRA; SINGH, Y V; MEENA, M C; DAS, T K; SEPAT, S; VERMA, R K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during kharif and rabi 2014-2016 at ICAR-IARI, New Delhi to study the system productivity, economics and energetics of maize (Zea mays L.) and wheat (Triticum aestivum L.) as influenced by crop residue (CR) and potassium (K) management under zero till maize-wheat system. The experiment was laid out in split plot design with four CR levels (0, 2, 4 and 6 t/ha) and five K levels (0, 50%, 100%, 150% RDK [recommended dose of K] and 50% RDK+Potassium solubilizing bacteria, KSB). Results revealed that significantly higher system productivity, output energy, specific energy and highest energy intensiveness, actual change in available K were found with 4.0-6.0 t/ha CR. Maximum B: C ratio in maize-wheat system was observed with No CR followed by 2.0-4.0 t/ha CR. Highest net energy returns, energy use-efficiency, energy productivity and lowest input energy (351- 395%) in both crops were registered with No CR fb 2.0-4.0 t/ha CR. Among K management, 50% RDK+KSB was significantly superior over rest levels. The maximum system net returns, B:C ratio, output energy, net energy returns, energy use-efficiency and energy productivity were found in 50% RDK+KSB and consumed only 0.34-0.35% higher input energy over no K in maize and wheat. Change in available K was more in 150% RDK fb 50% RDK+KSB and 100% RDK. Thus, a combination of 2.0-4.0 t/ha CR retention and 50% RDK along with seed inoculation with KSB improved system productivity, net returns and energetic parameters in zero tillage maize-wheat system, and brought positive change in available K and hence can be recommended for adaptation by the farmers.